Elastography for the pancreas: Current status and future perspective - Kawada, Natsuko (World J Gastroenterol, 2016)
Elastography for the pancreas can be performed by either ultrasound or endoscopic ultrasound (EUS). There are two types of pancreatic elastographies based on different principles, which are strain elastography and shear wave elastography. The stiffness of tissue is estimated by measuring the grade of strain generated by external pressure in the former, whereas it is estimated by measuring propagation speed of shear wave, the transverse wave, generated by acoustic radiation impulse (ARFI) in the latter. Strain elastography is difficult to perform when the probe, the pancreas and the aorta are not located in line. Accordingly, a fine elastogram can be easily obtained in the pancreatic body but not in the pancreatic head and tail. In contrast, shear wave elastography can be easily performed in the entire pancreas because ARFI can be emitted to wherever desired. However, shear wave elastography cannot be performed by EUS to date. Recently, clinical guidelines for elastography specialized in the pancreas were published from Japanese Society of Medical Ultrasonics. The guidelines show us technical knacks of performing elastography for the pancreas.